2018
DOI: 10.1021/acs.jafc.8b01727
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Magnesium Hydroxide Nanoparticles As an Alternative to Cu Biocide for Crop Protection

Abstract: In agriculture, prolonged use of copper biocides increases the risk of development of Cu resistance and its accumulation in soil, demanding an alternative. In this paper, we report antimicrobial magnesium hydroxide nanoparticles (NPs) as an alternative to Cu biocides with low cytotoxicity. To improved bioavailability, Mg hydroxide NPs were synthesized followed by coating with water-soluble capping agents, trisodium citrate (zeta potential, ξ = -22 mV) or betaine (ξ = +35 mV). Electron microscopy study confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Engineered nanomaterials (ENMs) are expected to offer some benets in food safety and production, 16 however a lot of unknowns remain. Metals and metalloids of Ag, 17,18 Ti, 19,20 Mg, 21,22 Zn, [23][24][25][26] Mn 27,28 have been studied as potential substitutes for Cu but the registration process of a new active is very cumbersome. In an effort to identify a short-term solution using the same Cu active ingredient, Strayer-Scherer et al demonstrated that ultra-small size Cu nanoparticles (NPs) can provide comparable protection against Cu-tolerant strains of X. perforans at Cu concentrations ve times lower than commercial formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Engineered nanomaterials (ENMs) are expected to offer some benets in food safety and production, 16 however a lot of unknowns remain. Metals and metalloids of Ag, 17,18 Ti, 19,20 Mg, 21,22 Zn, [23][24][25][26] Mn 27,28 have been studied as potential substitutes for Cu but the registration process of a new active is very cumbersome. In an effort to identify a short-term solution using the same Cu active ingredient, Strayer-Scherer et al demonstrated that ultra-small size Cu nanoparticles (NPs) can provide comparable protection against Cu-tolerant strains of X. perforans at Cu concentrations ve times lower than commercial formulations.…”
Section: Introductionmentioning
confidence: 99%
“…This paper reviews specialized coatings on metal and metal-oxide NP formulations for the purpose of inhibiting agglomeration and promoting targeted application. Metal and metal-oxide NPs are widely explored in agricultural applications because they may supply essential elements as fertilizers, and at higher doses, as pesticides [1][2][3][4][5][6][7]. Nanoscale silicon dioxide, copper oxide, and zinc oxide can support crops against drought and alleviate heavy metal contamination [8,9].…”
Section: Nanoparticles In Agriculturementioning
confidence: 99%
“…Recently, metal oxides (TiO 2 , ZnO, CuO, MgO, etc.) and magnesium hydroxide (MgOH) 2 nanoparticles (NPs) with high surface-to-volume ratios were shown to possess antibacterial properties, and these materials are finding applications in biomedicine and agriculture [4][5][6][7][8][9]. In the case of (Cu)-based antimicrobials, which are currently widely used by the agricultural sector for disease control, the trend is to minimize their usage due to potential toxicity and reduced effectiveness in several cases (EPA-HQOPP-2010-0212).…”
Section: Introductionmentioning
confidence: 99%